PENGARUH SUHU PEMADATAN TERHADAP STABILITAS DAN FLOW BAHAN LAPIS TIPIS ASPAL BETON (LATASTON) - ,, Marjono (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2017)
In Indonesia, the highway pavement construction still use flexible pavement construction (Flexible Pavement). One of the problems often faced in the implementation time is to keep the temperature mix asphalt is still in the limit, This happens because it is associated with the weather conditions and the length of the transport of asphalt mixing point to the location. So often happens temperature asphalt mix location is at the lowest limit, and potentially non-fulfillment of the temperature required at this stage to stage compaction. This will result in the implementation of the road pavement quality and age will affect the service life of pavement construction. On the basis that the researchers took the title